Cocaine self-administration in mice with forebrain knock-down of trpc5 ion channels - Pomrenze, Matthew B (F1000Research, 2013)
Canonical transient receptor potential (TRPC) channels are a family of non-selective cation channels that play a crucial role in modulating neuronal excitability due to their involvement in intracellular Ca2+ regulation and dendritic growth. TRPC5 channels a) are one of the two most prevalent TRPC channels in the adult rodent brain; b) are densely expressed in deep layer pyramidal neurons of the prefrontal cortex (PFC); and c) modulate neuronal persistent activity necessary for working memory and attention. In order to evaluate the causal role of TRPC5 in motivation/reward-related behaviors, conditional forebrain TRPC5 knock-down (trpc5-KD) mice were generated and trained to nose-poke for intravenous cocaine. Here we present a data set containing the first 6 days of saline or cocaine self-administration in wild type (WT) and trpc5-KD mice. In addition, we also present a data set showing the dose-response to cocaine after both groups had achieved similar levels of cocaine self-administration. Compared to WT mice, trpc5-KD mice exhibited an apparent increase in self-administration on the first day of cocaine testing without prior operant training. There were no apparent differences between WT and trpc5-KD mice for saline responding on the first day of training. Both groups showed similar dose-response sensitivity to cocaine after several days of achieving similar levels of cocaine intake.